Effectiveness And Contribution Of The Hotel Tax Revenue In Optimization Of Original Local Government Revenue In Banyuwangi Regency - Galih Wicaksono; Yeni Puspita; Lilis Setyaningsih; Boedijono Boedijono (Educoretax, 2023)
The Covid-19 pandemic has resulted in a decrease in domestic and foreign tourist arrivals in Banyuwangi Regency, this is due to one of the government's policies, namely Large-Scale Social Restrictions (PSBB). This has resulted in the tourism sector tax being threatened not optimally, especially the hotel tax. This study aims to determine the level of effectiveness and contribution of Hotel Tax to Regional Original Income (PAD) in Banyuwangi Regency, and to find out what strategies are carried out in optimizing hotel tax revenues to optimize Original Local Government Revenue (PAD). The population of this study is local taxpayers in Banyuwangi Regency, by taking samples from restaurant taxpayers. Data collection techniques are through interviews with the Regional Revenue Agency (BAPENDA) and literature studies of data obtained from BAPENDA and BPS, especially regarding restaurant tax data, PAD, tourists, and strategies in restaurant tax policies. This study resulted in the finding that when the number of victims exposed to Covid-19 was relatively high, it had an impact on the decrease in the number of hotel room occupants, as a result, hotel revenue decreased and affected Hotel Tax Revenue which decreased. The effectiveness of hotel tax revenue is always in the very effective category, because it always meets the set targets. The hotel tax contribution to PAD is always in the very low category because the PAD increase is very significant, not followed by a significant increase in hotel tax. The strategy in optimizing hotel tax revenue is by providing a policy in the form of eliminating fines for late reporting or payments which aims to provide relief to taxpayers so that they are not burdened with their tax obligations so that they continue to carry out their tax obligations.